2007
DOI: 10.2466/pr0.100.4.1115-1120
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and Posttraumatic Stress Disorder in a Rural Primary Care Population in South Africa

Abstract: The aim of this study was to assess trauma events experienced and PTSD among 250 consecutive rural primary clinic patients (all Black Africans, 24% male and 76% female; M age 31.1 yr., SD = 11.8; range 18-65 years) in South Africa using the Trauma History Questionnaire and the PTSD Checklist-Civilian Version, interview administered. Results indicated that the mean number of traumatic events reported was 3.5 (SD = 2.9, range = 0-19) and was significantly higher among men (M= 4.9, SD = 3.5) than women (M = 3.0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…For example, Kessler et al in the US National Comorbidity Survey reported rates of between 51 and 61% for traumatic events, while Rosenman in the Australian National Survey of Mental Health and Wellbeing reported that 57% of the population had experienced a traumatic event (28,29). The few available studies (mostly conducted among adolescent populations) on community prevalence of traumatic events in Africa demonstrate a higher prevalence rate ranging from 67 to 98% (31)(32)(33). These observations suggest that strict comparisons of rates between countries should be interpreted with caution, as not only are estimates affected by ascertainment procedure but also by when the estimates are made.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kessler et al in the US National Comorbidity Survey reported rates of between 51 and 61% for traumatic events, while Rosenman in the Australian National Survey of Mental Health and Wellbeing reported that 57% of the population had experienced a traumatic event (28,29). The few available studies (mostly conducted among adolescent populations) on community prevalence of traumatic events in Africa demonstrate a higher prevalence rate ranging from 67 to 98% (31)(32)(33). These observations suggest that strict comparisons of rates between countries should be interpreted with caution, as not only are estimates affected by ascertainment procedure but also by when the estimates are made.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that our measure of PTSD is not diagnostic, and symptoms were not assessed specifically for a given trauma; therefore, the proportion meeting screening criteria for PTSD may overstate the true sample prevalence. Nevertheless, data from clinic-based studies in South Africa have reported similarly high rates of PTSD, ranging from 12% to 20% (Carey et al, 2003;Peltzer et al, 2007). For comparison, the prevalence of PTSD among adults in the United States is 3.4%, as assessed by the Collaborative Psychiatric Epidemiologic Surveys (Pagoto et al, 2012).…”
Section: Discussionmentioning
confidence: 99%